Impfungen im Alter - Kwetkat, A.; Heppner, Hans Jürgen; Hagel, S.; M, Wutzler (Pneumologe, 2014)
The aging immune system, so-called immunosenescence, is well documented as being the cause of increased infection rates and severe, often complicated courses of infections in the elderly with increased morbidity and mortality rates. Furthermore, it can lead to decreased efficacy of vaccinations. The administration of stronger immunogenic vaccines can be beneficial in the elderly. Implementing vaccination recommendations for the elderly by the Ständige Impfkommission (STIKO, Standing Vaccination Committee) can reduce the burden of infectious diseases by prevention of infections or reduction of the severity of infections. The following vaccinations are recommended by STIKO for all persons aged 60 years and above: annual influenza vaccination (additionally all nursing home residents independent of age), once only pneumococcal polysaccharide vaccination, completion of incomplete tetanus and diphtheria vaccinations (Td) as well as regular revaccination. All adults should be vaccinated once only against pertussis with the combined Td and acellular pertussis (Tdap) vaccine. Meanwhile, pneumococcal conjugate vaccine is authorized for administration in adults but is not yet recommended by the STIKO which also applies to the vaccine for prevention of herpes zoster and postherpetic neuralgia. A lifelong course of vaccination may help to attenuate the effect of immunosenescence.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Aged; Herpes zoster; Influenza vaccine; Pneumococcal vaccine; Senescence